2020
DOI: 10.1093/pcp/pcaa017
|View full text |Cite
|
Sign up to set email alerts
|

Downregulation of a Mitochondrial NAD+ Transporter (NDT2) Alters Seed Production and Germination in Arabidopsis

Abstract: Despite the fundamental importance of nicotinamide adenine dinucleotide (NAD+) for metabolism, the physiological roles of NAD+ carriers in plants remain unclear. We previously characterized the Arabidopsis thaliana gene (At1g25380), named AtNDT2, encoding a protein located in the mitochondrial inner membrane, which imports NAD+ from the cytosol using ADP and AMP as counter-exchange substrates for NAD+. Here, we further investigated the physiological roles of NDT2, by isolating a T-DNA insertion line, generatin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
38
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 20 publications
(40 citation statements)
references
References 49 publications
2
38
0
Order By: Relevance
“…Likewise, the abundance of mitochondrial-encoded subunits in maize and rice was already high at the early stages in germination, as was porin [ 21 , 23 ], compared to in barley where it steadily increased over time to peak at 24 or 48 h. Moreover, overall, organelle translation machineries were upregulated in Arabidopsis compared to barley ( Figure 5 B), suggesting that mitochondrial capacity was overall increasing rapidly in Arabidopsis. Given the important role of components involved in mitochondrial biogenesis for the timing of germination, such as Tim17-1 ([ 44 ], and overall the importance of mitochondrial function for germination [ 14 , 60 , 61 , 62 ]), the kinetics of mitochondrial biogenesis during germination may play an important role in determining the speed of germination.…”
Section: Discussionmentioning
confidence: 99%
“…Likewise, the abundance of mitochondrial-encoded subunits in maize and rice was already high at the early stages in germination, as was porin [ 21 , 23 ], compared to in barley where it steadily increased over time to peak at 24 or 48 h. Moreover, overall, organelle translation machineries were upregulated in Arabidopsis compared to barley ( Figure 5 B), suggesting that mitochondrial capacity was overall increasing rapidly in Arabidopsis. Given the important role of components involved in mitochondrial biogenesis for the timing of germination, such as Tim17-1 ([ 44 ], and overall the importance of mitochondrial function for germination [ 14 , 60 , 61 , 62 ]), the kinetics of mitochondrial biogenesis during germination may play an important role in determining the speed of germination.…”
Section: Discussionmentioning
confidence: 99%
“…As a result, disruption of ABA metabolism gives rise to increased stomatal numbers (Tanaka et al ., 2013). A recent functional characterization of NDT1 and NDT2 mutants had shown reduced seed germination, a phenotype previously explained by possible enhanced ABA levels and/or signaling (de Souza Chaves et al ., 2019; Feitosa‐Araujo et al ., 2020). Furthermore, NAD(P)(H) homeostasis has previously been associated with ABA biosynthesis and signaling (Hunt and Gray, 2009a; Arias et al ., 2018; Wei et al ., 2020; Hong et al ., 2020).…”
Section: Resultsmentioning
confidence: 99%
“…In fact, the ratio of NAD to NADP, as well as the redox status of each pool is highly dependent on the specific subcellular compartment (Kulkarni and Brookes, 2019). In plant cells, specialized transport proteins are responsible for the provision of NAD + to the organelles (Palmieri et al ., 2009; Bernhardt et al ., 2012; Gakière et al ., 2018; de Souza Chaves et al ., 2019; Feitosa‐Araujo et al ., 2020). Two carrier proteins located in the inner mitochondrial membrane, namely NDT1 ( At 2g47490) and NDT2 ( At 1g25380), and one targeted to the peroxisomal membrane, PXN ( At 2g39970), have been previously identified and biochemically characterized as NAD + transporters in Arabidopsis (Palmieri et al ., 2009; Agrimi et al ., 2012; Bernhardt et al ., 2012; Van Roermund et al ., 2016; de Souza Chaves et al ., 2019).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Silencing of the mitochondrial glutamate carrier in colorectal tumor cells resulted in a relatively small increase in cellular glutamate content whereas the aspartate level was reduced by ~45% (84). In plants, studies of mitochondrial carrier mutants reported to date are unable to directly link growth and/or metabolic phenotype with gene function (8587). It is possible that, apart from functional redundancy, changes in metabolic fluxes occur without altering overall metabolite pool or physiology, which can only be captured by sensitive measurements under specific external conditions.…”
Section: Discussionmentioning
confidence: 99%